Safety and Efficacy of Bedaquiline in Drug Resistant Tuberculosis: A Hospital-based Prospective Observational Study - Saima Ejaz; Imrana Masood; Md Mokarram Ali; Ummul Baneen; Zuber Ahmad; Rakesh Bhargava (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Tuberculosis (TB) is a chronic infectious disease that continues to cause significant morbidity and mortality in developing nations. The emergence of Drug Resistant Tuberculosis (DR-TB) has further aggravated the problem. The treatment of DR-TB is challenging due to poor compliance, stemming from drug toxicity and the long duration of treatment. Bedaquiline (BDQ), a novel drug, has shown promising results in terms of safety and efficacy for the treatment of Multidrug Resistant TB (MDR-TB). Aim: To evaluate the safety and efficacy of BDQ in patients with DR-TB. Materials and Methods: This was a prospective, observational, hospital-based study carried out in the Department of Respiratory Medicine at JNMC, Aligarh, Uttar Pradesh, India, over a period of two years from December 2020 to November 2022. A total of 303 patients were enrolled. BDQ treatment was initiated after satisfying the inclusion criteria and patients were monitored for Adverse Events (AE). The study evaluated outcomes in terms of sputum conversion and clinical improvement. A follow-up was conducted for six months after the completion of therapy. Data entry was performed on Microsoft Excel and the final analysis was conducted thereafter. Results: Out of 303 patients, successful outcomes with BDQ were observed in 272 (89.77%) patients who were cured. Sixteen patients died (5.28%), 10 (3.30%) cases were lost to follow-up and in 5 (1.65%) patients, BDQ was discontinued due to adverse effects. Clinical improvement, in terms of an increase in body weight, improvement in symptoms and radiological improvement, was observed in 265 (97.43%) patients. Conclusion: The study concludes that BDQ demonstrates promising safety and efficacy, establishing itself as a valuable option for the treatment of DR-TB.